Improvement of Student Learning Outcomes after Following Learning With The Media Marketplace - Hendri Gunawan; M. Toyib (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Education is an important component for students in preparing to enter the world of work. education can be completed by students well through the learning process in college. In learning, of course, there are outputs or results that can measure students' abilities. Benchmarks can be seen from student learning outcomes after using the media marketplace. Marketplace is one that can be used to market entrepreneurial products. The purpose of this study is to improve student learning outcomes after participating in learning with the media marketplaceThe research method used qualitative methods, namely to determine the increase in student learning outcomes after participating in learning with the media marketplace. The data analysis techniques used was tests. Based on the results of this study, it is known that seen from the average student score increased from 84.88 to 86, 24 after the use of marketplace learning media, this means that the use of marketplace learning media can improve student learning outcomes in accounting education study programs.